Collaborative Governance: the Role of the House of Representatives in the Relocation of Bong Suwung Localization, Yogyakarta City - Nailul Himam; Sugiyanto Sugiyanto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The issue of prostitution in Yogyakarta, especially in the Bong Suwung area, reflects the complexity that involves social, economic, and legal aspects. Despite regulations, prostitution practices continue to increase, presenting challenges in law enforcement and individual protection. The process of relocating Bong Suwung by PT KAI faced protests from residents who felt they were not treated fairly. In this context, the application of the concept of Collaborative Governance is important, with collaboration between the DPRD, local governments, and the community to achieve more humane and equitable solutions. The DPRD plays a role as a mediator, accommodating the aspirations of the community and ensuring transparency in the relocation process. This research shows that success in addressing prostitution and relocation issues is highly dependent on the collaborative capabilities of various actors, as well as the application of Collaborative Governance principles to create responsive public policies and reduce potential conflicts